Household and Economy: Toward a New Theory of Population and Economic Growth - Nerlove, Marc (Journal of Political Economy, 1974)
It is somewhat unusual to begin the treatment of a subject with a warning against attaching too much importance to it; but in the case of economics, such an injunction is quite as much needed as explanation and emphasis of the importance it really has.It is characteristic of the age in which we live to think too much in terms of economics, to see things too predominantly in their economic aspect... .There is no more important prerequisite to clear thinking in regard to economics itself than is recognition of its limited place among human interests at large.